The quality of eligible collateral and monetary stability: An empirical analysis - Philipp Lehmbecker (Research On Money in the Economy (ROME), 2008)
The central banking literature regards central bank independence and a transparent monetary policy as best suited to achieve and safeguard monetary stability. The existing empirical literature, however, failed in establishing a solid ground for this consensus. This paper sheds some new light on the empirical evidence on determinants of monetary stability. In addition, it expands the current research agenda by considering a neglected factor: The quality of eligible collateral (QEC). Recently, the U. S. subprime crisis has shown that a weak collateralization of credits may have massive economic implications, entailing severe perturbations of the international financial system. This paper focuses on central bank lending and investigates to what extent the quality of eligible collateral is able to explain inflation employing the first comprehensive dataset to assess the significance of QEC for monetary stability. Data have been collected using an online questionnaire that was answered by central bank officials. For the period 1990 to 2003 and a sample of 62 countries a robust negative and statistically significant correlation between QEC and average inflation is found. This result is robust to the use of control variables from the literature on institutional determinants of monetary stability. These findings have to be regarded as establishing QEC as one pivotal element of a theory of central banking. Collateralisation of the issuance of money and the elimination of financing the government deficit directly via the central bank can be seen as necessary conditions for achieving monetary stability. Good central bank money should be backed by the liable property of creditors to safeguard monetary stability. This finding can be utilized by policy makers especially in less developed and transition countries on their way towards a more stable economic development.
Keywords: E58; E42; B59; P14; 330; Monetary economics; monetary theory; inflation; collateral; central banks; property; property economics; central bank independence